Effect of Power and Time in Pectin Production from Cocoa Pod Husk Using Microwave-Assisted Extraction Technique - Maya Sarah; Hisham Hisham; Mushila Rizki; Ricka Erwinda (International Journal of Renewable Energy Development, 2020)
Investigation on microwave technique to extract pectin from cocoa pod husk in this study carries out using citric acid and hydrochloric acid (HCl). Extraction proceeds at various microwave powers (180, 300, 450, 600 Watt) and irradiation periods (10, 15, 20, 25, 30 minutes). This study observed effect of power and time to yield and quality of pectin.  Yield of pectin increased at elevated power and time either with citric acid or HCl solvent. Overall pectin quality in this study meet the IPPA quality factor exclude water content which relatively higher. MAE treatment with citric acid using microwave power of 300 Watt for 30 minutes resulted yield of 42% and high pectin quality as compare to MAE treatment with HCl. The best pectin product in this study has moisture content of 8%, ash content of 10%, equivalent weight of 714.29 mg, methoxyl content of 4.8% and galacturonate level of 43%. ©2020. CBIORE-IJRED. All rights reserved